Efficient Synthesis and Characterization of Lidocaine Analogue N-Ethyl-N-((8-methylquinazolin-2-yl)methyl)ethanamine - Woo, Sang Woo; Shim, Jae Ho; Han, Jihye; Lim, Jin Ju; Kim, Hyeon Soo (SynOpen, 2026)
N-Ethyl-N-((8-methylquinazolin-2-yl)methyl)ethanamine, a novel quinazoline-based lidocaine analogue, was efficiently synthesized on a 10-g scale via a seven-step process with 44.3% overall yield. Key synthetic transformations achieved excellent yields (80–92%): LiAlH4 reduction, diethylamine substitution, MnO2 oxidation, and intramolecular cyclization. Comprehensive in vitro evaluation revealed favorable safety and pharmacological profiles. Toxicity assays across HEK293, PC12, and H9c2 cell lines demonstrated IC20 values of 5.8–10.8 μM with appropriate safety margins. Caco-2 permeability studies showed high membrane penetration (Papp: 1.35 × 10–8 cm/s, efflux ratio: 0.89), comparable to lidocaine. Critically, it exhibited 2.64-fold enhanced potency toward Nav1.5 sodium channels in inactivated state (IC50 = 8.86 ± 1.2 μM vs. lidocaine 23.40 ± 2.6 μM) while maintaining state-dependent blocking characteristics. Metabolic stability was superior to lidocaine, with hepatic half-life of 23.26 minutes (26% longer). These results, combining enhanced pharmacological potency, acceptable toxicity, superior metabolic stability, and reliable synthesis, position N-ethyl-N-((8-methylquinazolin-2-yl)methyl)ethanamine as a promising next-generation local anesthetic candidate warranting further clinical development.
Keywords: lidocaine analogue; quinazoline; local anesthetic; sodium channel antagonist; patch-clamp electrophysiology; in vitro toxicology; ADME